2023
DOI: 10.1186/s13020-023-00751-7
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine in the era of immune checkpoint inhibitor: theory, development, and future directions

Abstract: Immune checkpoint inhibitors (ICIs) have revolutionized cancer management and have been widely applied; however, they still have some limitations in terms of efficacy and toxicity. There are multiple treatment regimens in Traditional Chinese Medicine (TCM) that play active roles in combination with Western medicine in the field of oncology treatment. TCM with ICIs works by regulating the tumor microenvironment and modulating gut microbiota. Through multiple targets and multiple means, TCM enhances the efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…However, cancer cells can exploit these checkpoints to evade detection and destruction by the immune system, allowing tumors to evade immune surveillance ( 71 ). TCM compounds have shown promise in their ability to modulate immune checkpoint molecules, including PD-1, CTLA-4, and LAG-3 ( 72 ). One such example is the Gegen Qinlian decoction (GQD), a classical TCM formula.…”
Section: The Regulatory Effects Of Tcm Monomers and Compounds On Tmementioning
confidence: 99%
See 1 more Smart Citation
“…However, cancer cells can exploit these checkpoints to evade detection and destruction by the immune system, allowing tumors to evade immune surveillance ( 71 ). TCM compounds have shown promise in their ability to modulate immune checkpoint molecules, including PD-1, CTLA-4, and LAG-3 ( 72 ). One such example is the Gegen Qinlian decoction (GQD), a classical TCM formula.…”
Section: The Regulatory Effects Of Tcm Monomers and Compounds On Tmementioning
confidence: 99%
“…Moreover, the integration of TCM with conventional cancer therapies like chemotherapy and radiation, paves the way for synergistic effects and novel therapeutic avenues. Notably, studies have indicated that TCM compounds can enhance the effectiveness of these treatments by sensitizing tumor cells to cytotoxic agents, modulating the tumor microenvironment, and mitigating treatment-associated side effects ( 72 ). Furthermore, the combination of TCM with emerging immunotherapies, such as cancer vaccines and chimeric antigen receptor (CAR) T-cell therapy, embraces a promising future in unleashing robust anti-tumor immune responses and ultimately improving patient outcomes.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…TCM has been combined with other anti-cancer treatment modalities, including radiotherapy, chemotherapy, and targeted therapy, with an aim to enhance the treatment efficacy and alleviate adverse drug effects. In recent years, numerous studies also suggest that TCM could modulate the TME to reverse ICI resistance, potentiate clinical efficacy, and reduce the severity of immune-related adverse events (irAEs) [ 208 , 209 ]. The repurposing use of a few representative TCM drugs in potentiating ICI efficacy and their mechanisms of resistance circumvention are described below.…”
Section: Representative Repurposed Drug Candidates To Overcome Ici Re...mentioning
confidence: 99%
“…2 In terms of disease treatment modalities, the diversity of TCM components, multi-targets, and multi-pathways have made the study of drug targets also become extremely difficult to study. 3 Therefore, finding new alternatives is being progressively considered.…”
Section: Introductionmentioning
confidence: 99%